Yiannis Papadatos and Chrysa Sofianou Livari Skiadi. A Minoan cemetery in southeast Crete. Volume I. Excavation and finds - Déderix , Sylviane (Journal of Greek Archaeology, 2016)
The early 21st century is an exciting period for Minoan funerary studies. Over the last 15 years, a series of tombs and cemeteries that had been unearthed decades earlier have been extensively published, old excavated assemblages have been (re)studied, and new burial sites have been discovered. This profusion of fresh data has triggered a renewed interest in Minoan, and especially Prepalatial, mortuary practices. Fed by the theoretical, methodological, and scientific developments that took place in the archaeology of death from the 1980s onwards, recent studies offer novel perspectives on this enriched dataset. In this way, tomb types and grave goods are no longer seen as passive reflections of the status of the deceased; quite the contrary, it is now well acknowledged that funerary practices played an active role in the negotiation of social identities and relationships among the living.